2001
DOI: 10.1016/s0022-5347(05)65541-3
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamic and Clinical Evidence of Acute Inhibitory Effects of Intravesical Nociceptin/Orphanin Fq on Detrusor Overactivity in Humans: A Pilot Study

Abstract: Our results demonstrate that nociceptin/orphanin FQ is able to elicit a robust inhibitory effect on voiding reflex in group 2 but not 1. The ideal dosage, route of administration of nociceptin/orphanin FQ and treatment interval are not yet established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…These pharmacological features are highly desirable especially for investigating those conditions and states in which a selective and prolonged stimulation of NOP receptor is beneficial, including anxiety states [21,28], drug addiction [15,48], anorectic conditions [16], spinal analgesia (as indicated by laboratory animals [54] as well as primate [35] studies), cough and possibly other respiratory diseases [40], acute heart failure [26,34], and, as indicated by clinical studies, urinary incontinence due to overactive bladder [37][38][39]. Peak changes in mean arterial pressure and heart rate produced immediately following i.v.…”
Section: Discussionmentioning
confidence: 99%
“…These pharmacological features are highly desirable especially for investigating those conditions and states in which a selective and prolonged stimulation of NOP receptor is beneficial, including anxiety states [21,28], drug addiction [15,48], anorectic conditions [16], spinal analgesia (as indicated by laboratory animals [54] as well as primate [35] studies), cough and possibly other respiratory diseases [40], acute heart failure [26,34], and, as indicated by clinical studies, urinary incontinence due to overactive bladder [37][38][39]. Peak changes in mean arterial pressure and heart rate produced immediately following i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether these results indicate that ORL1 receptors are present at several sites for the integration of the micturition reflex, and that their activation may produce both excitatory and inhibitory effects, depending on the route of administration and the experimental conditions. Lazzeri et al (2001) investigated the urodynamic and clinical effects of intravesical instillation of nociceptin/ orphanin FQ (1 M) in five normal subjects and nine patients with neurogenic detrusor overactivity refractory to standard therapy. Intravesical instillation of nociceptin/orphanin FQ produced no significant functional changes in the controls.…”
Section: Peripheral Targetsmentioning
confidence: 99%
“…28 A study in humans investigated the effect of nociceptin/orphanin FQ in healthy subjects and patients with neurogenic detrusor overactivity. 29 After intravesical instillation of 1 mM nociceptin/orphanin FQ, a significant increase in mean bladder cystometric capacity and volume threshold for the appearance of neurogenic detrusor overactivity in patients compared to healthy subjects group was observed. However, the clinical and urodynamic effect lasted for 2 weeks only.…”
Section: Intravesical Nociceptin/orphanin Fqmentioning
confidence: 90%
“…In this study, it was also hypothetised that nociceptin/orphanin FQ acts on the afferent limb of the micturition reflex in spinal cord injured patients and activates inhibitory opoid receptorlike OP 4 expressed on afferent type C fibres of the bladder. 29 Recently, a randomised, placebo-controlled and double-blind study on 14 patients with neurogenic detrusor overactivity has been published and the results indicated that 1 mM nociceptin/orphanin FQ provides an acute inhibitory effect on the micturition reflex in this patient population. 30 The bladder capacity and the threshold for the appearance of detrusor overactivity increased significantly from 139 to 240 ml and from 84 to 201 ml, respectively.…”
Section: Intravesical Nociceptin/orphanin Fqmentioning
confidence: 99%